2022
DOI: 10.1128/mbio.03561-21
|View full text |Cite
|
Sign up to set email alerts
|

Novel CRK-Cyclin Complex Controls Spindle Assembly Checkpoint in Toxoplasma Endodyogeny

Abstract: The rate of Toxoplasma tachyzoite division directly correlates with the severity of the disease, toxoplasmosis, which affects humans and animals. Thus, a better understanding of the tachyzoite cell cycle would offer much-needed efficient tools to control the acute stage of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 71 publications
2
23
2
Order By: Relevance
“…We found that in addition to interaction with TgCycP1 and TgCycP2, TgCrk2 myc kinase formed a specific complex with the atypical cyclin TgCyc5 (TGME49_293280) ( Fig. 1D ) ( 22 ). While interaction with TgCycP1 and TgCycP2 may have been attributed to the presence of tachyzoites and early-stage bradyzoites, the TgCrk2/TgCyc5 complex was formed only under bradyzoite-induction conditions.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that in addition to interaction with TgCycP1 and TgCycP2, TgCrk2 myc kinase formed a specific complex with the atypical cyclin TgCyc5 (TGME49_293280) ( Fig. 1D ) ( 22 ). While interaction with TgCycP1 and TgCycP2 may have been attributed to the presence of tachyzoites and early-stage bradyzoites, the TgCrk2/TgCyc5 complex was formed only under bradyzoite-induction conditions.…”
Section: Resultsmentioning
confidence: 98%
“…1D ). Analysis of developmentally competent ME49 tachyzoites revealed that TgCrk2 kinase formed an equivalent complex with another P-cyclin TgCycP2 (TGME49_305330) ( 22 ). To find out whether the TgCrk2 cyclin partners change during bradyzoite development, TgCrk2 myc complexes were isolated from the ME49 strain that was grown for 3 days under alkaline conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations